Analysis Of Health Service Management Strategies On Patient Satisfaction At The Neighborhood Clinic - Dewi Agustina; Dellya Silfani; Hariyani, Elva; Farah Sabila; Lailatul Mahpuja Dasopang; Risky Andreansyah; Ulfiyah Az-Zahra Dahlan; Wulan Andika (Jurnal EduHealth, 2024)
Public health plays a crucial role in determining the prosperity of a country. A high level of health reflects the government's success in organizing and implementing effective health policies. Optimal health services and community empowerment are important factors in creating a high level of health. In writing this article, a qualitative descriptive research method was used. This research was carried out by conducting in-depth interviews by interviewing research instruments (resources) in order to obtain the required information or data. The information obtained after conducting interviews is presented in the article using qualitative descriptive methods. In terms of service, the service provided at the Simpang Tuntungan clinic is a friendly welcome and listening to every complaint of patients who come for treatment. It has a suggestion box, which aims to enable patients who come for treatment to provide assessments, suggestions and also submit/complaints when seeking treatment here. Does not differentiate between general patients and BPJS patients. The Simpang Tuntungan clinic applies 5 qualities of service at the Simpang Tuntungan clinic: form/appearance (tangible), reliability, responsiveness, assurance and empathy. The health services provided by the Tuntungan Clinic are good and have a positive impact, namely patient satisfaction.